Fertility and the Professional Activity of Women in Poland and Other Eu Countries in the Years 2004–2014 - Rękas, Magdalena (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2017)
The “new demography of Europe” is characterised by consolidation of the recovery process of generations below the generational replacement level (a pronounced decline in fertility rates to low levels), a longer human life span and increased professional activity among women. The new demography has been affected to a great extent by the current economic policies of EU countries, as well as the problems they have had providing for future growth and economic development. The aim of this article is to present and analyse the relationship between fertility and women’s professional participation in Poland and other EU countries in the period 2004–2014. The article contains a review of theories addressing the impact of having a child on the professional activity of women and an analysis of data from Eurostat statistics using simple statistical methods and Pearson’s correlation coefficient. The results of the report Bilans kapitału ludzkiego w Polsce (The Study of Human Capital in Poland, 2015) show the influence of the number of children on the economic activity of women. As a result of the study, it is indicated that in the vast majority of EU countries, the employment rate for women is strongly linked to fertility levels. In Poland’s case, moreover, the number of children a woman has is a key factor in her economic activity – the higher the number of children, the lower her economic activity will be.